PENGARUH MODEL PEMBELAJARAN LOGAN AVENUE PROBLEM SOLVING (LAPS-HEURISTIK) TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA PEMBELAJARAN IPAS SISWA KELAS V SDN 106146 MULIOREJO T.A 2025/2026 - Eva Lina Pandiangan; Imelda Free Unita Manurung; Zainuddin Muchtar; Winara; Lala Jelita Ananda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of the Logan Avenue Problem Solving (LAPS-Heuristic) learning model on students' problem-solving abilities in science learning, specifically on the topic of Harmony in Ecosystems, for fifth grade students of SDN 106146 Muliorejo in the 2025/2026 academic year. The research employed a quasi-experimental design with a nonequivalent control group design. The sample consisted of 41 students, divided into an experimental group of 21 students who learned using the LAPS-Heuristic model and a control group of 20 students who learned using the Problem Based Learning (PBL) model. The research instrument comprised ten essay questions that had been tested for validity, reliability, difficulty level, and discriminating power, and was declared suitable for use. The results showed that the average posttest score of the experimental group was 84.14, higher than that of the control group which was 76.15. Hypothesis testing using the Independent Samples t-test yielded a significance value of less than 0.001, indicating a significant difference between the test results of the two groups. The N-Gain Score calculation showed an average increase of 59.91% (moderate category) for the experimental group, higher than that of the control group which was 42.53% (moderate category). Therefore, the LAPS-Heuristic learning model has a positive and significant effect on students' problem-solving abilities of fifth-grade students of SDN 106146 Muliorejo in the 2025/2026 academic year in elementary science learning.